Differential biomass allocation to plant organs and their allelopathic impact on the growth of crop plants: A case study on the invasibility of Ageratum conyzoides in Indian dry tropics - CHAUDHARY, NIDHI; NARAYAN, RUP; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2015)
Variation in biomass allocation strategy of the alien winter annual billy goat weed (Ageratum conyzoides L.) was investigated for its invasiveness at two contrasting sites of occurrence in Indian dry tropical peri-urban region at longterm and recurrently infested site (LTI) and short-term infested (STI) site. Growth retardation impact of leaf, stem, root and reproductive part of this weed on maize and mung growths was also investigated. Compared to LTI site, the plants at STI site had higher mean basal diameter, leaf number, total plant biomass, leaf and reproductive mass fractions. Phenotypic plasticity was also higher here, albeit marginally. On the other hand, LTI plants had higher mean shoot length, belowground: aboveground biomass ratio, stem and root mass fractions. Biomass allocation to different components varied with ontogeny and site/soil conditions. While stem allocation increased with plant size at both sites, the leaf allocation generally declined. At any ontogenetic point, the reproductive and leaf allocations by plants were higher at STI compared to LTI. Root allocation at STI increased with plant size, whereas it decreased at LTI. Soil organic carbon significantly improved with increasing amount of residue of leaf, stem, root and reproductive part incorporated in soil. The leaf and root residue-amended soils recorded increasing growth retardation with increase in the amount of their incorporation in the soil.